Flooding and management of large fluvial lowlands: a global environmental perspective - Hudson, Paul F. (Cambridge Cambridge University press, 2021)
"Large fluvial lowlands are Earth's most distinctive and productive environments but are being rapidly degraded by human activities. Pressure on large rivers and deltas has increased tremendously over past decades because of flood control, urbanization, and increased dependence for food production This book examines human impacts on lowland rivers and discusses how these changes affect different types of riverine environments and flood processes, and how these "lessons" can be used to more sustainably manage large rivers and deltas. Surveying a global range of large rivers, including the Mekong, Nile, Sacramento, Danube, Huanghe, among others, the book especially examines management of the Rhine River in the Netherlands and the lower Mississippi in Louisiana. A particular focus of the book is on sedimentology and hydraulic engineering, which is described in a straightforward writing style accessible to a broad audience of advanced students, researchers, and practitioners in global environmental change, fluvial geomorphology and sedimentology, and flood and river management"--
Keywords: Floodplain management; River engineering; SCIENCE / Earth Sciences / Hydrology; SCIENCE / Earth Sciences / Hydrology